Lack of Radioprotective Potential of Ginseng in Suppressing Micronuclei Frequency in Human Blood Lymphocyte under Gamma Irradiation - YANTI LUSIYANTI; ZUBAIDAH ALATAS; MUKH SYAIFUDIN (Bogor Agricultural University, Indonesia, 2015)
Ginseng appears to be a promising radioprotector for therapeutic or preventive protocols capable of attenuating the deleterious effects of radiation on human normal tissue. This research addresses results on the study of radioprotective potential of ginseng on radiation induced micronuclei in lymphocyte cells in vitro. The peripheral blood samples were exposed to gamma rays at doses of 0.0, 0.5, and 1.0 Gy and then added with 0, 100, and 1000 ug/mL of ginseng extract. These treated samples were cultured for micronuclei (MN) examination using standard procedure. The evaluation of incubation with ginseng extract for 24 h before irradiation was also done. Our results showed that there was no radioprotective effect of ginseng addition to the frequency of MN in lymphocyte cells. Pre-incubation with ginseng extract before irradiation also did not effectively suppress the MN frequency. This research lacks to prove the ginseng’s radioprotective potential that maybe related to its immunomodulating capabilities and its capabilities in scavenging free radicals induced by radiation or in attenuating the deleterious effects of radiation and its important role in increasing levels of several cytokines.